Dynamic Assessment of Tunnels Subjected to Moving Train Loads (Case Study: Tunnel of Tehran Subway Line 3) - Aghabagher, Morteza Nasirivand; Samimi Namin, Farhad (Transportation Development Research, 2025)
The expansion of urban populations necessitates improvements in construction and the development of urban infrastructure. The creation of subway tunnels in urban centers has consistently faced considerable challenges and constraints. This study specifically focuses on one such issue: the intersection of subway lines with existing railway lines. The main aim of this research is to model the dynamic load imposed by a moving train on a section of the Tehran Metro Line 3 tunnel as it passes beneath the Tehran-Ahvaz intercity railway. To accomplish this, the dynamic load generated by the train’s movement is simulated, and a corresponding function for this load is derived. This function is subsequently incorporated into a numerical model of the tunnel, which is developed using the Finite Difference Method (FDM). Given that the tunnel is situated within soil, the environment surrounding it is regarded as a continuous equivalent medium. The results of this modeling are then compared with two analytical approaches. The comparison demonstrates a strong correlation between the results, thereby validating the accuracy of the findings from the computational model. Additionally, by assessing the most critical operational conditions for trains on the Tehran-Ahvaz railway, a safety factor of 2.34 is established, indicating the design’s robustness under the specified conditions.